Danish r and adjacent short stressed vowels - Heger, Steffen (Annual Report of the Institute of Phonetics University of Copenhagen, 1975)
This is a presentatior of the main features of the distributional pattern of Danish r and of some formant measurements of r-combinations. The possibility of describing /ɛ, œ/ after /r/ as ultra-short diphthongs is discussed.